Thyroid neoplasm in Graves' disease: A single center experience (Annals of Medical Research, 2022)
Aim: Different comments are stated in the studies about the association between Graves’ disease and thyroid neoplasms. The aim of this research was to evaluate the prevalance of thyroid neoplasm in patients with Graves’ disease who underwent thyroidectomy.Materials and Methods: A retrospective examination was made of 200 patients, who were followed up with the diagnosis of Graves' disease between 2008 and 2020. A total of 46 patients who underwent thyroidectomy were evaluated in the study. Euthyroidism was achieved in all patients before the operation.Results: Thyroidectomy for Graves’ disease was performed in 46 cases. Thyroid neoplasm was identified in the surgically-resected specimens of 12 patients (26.1%). The prevalence of thyroid neoplasm was higher in patients with nodules than in those without (p= 0.08). The level of white blood cells was higher in patients with neoplasm than in those without. The levels of thyroglobuline antibody and thyroid peroxidase, which are increased in autommune thyroiditis, were higher in patients without neoplasms than in those with neoplasm.Conclusion: In addition to careful physical examination, thyroid ultrasonography should be performed in patients with Graves’ disease. Surgery should be recommended for patients with suspicious or malignant findings on thyroid ultrasonography and fine needle aspiration biopsy. Also, increased white blood cell count and low thyroid autoantibody levels should raise suspicion of the presence of neoplasm.
Keywords: Graves’ disease; Nodule; Thyroid neoplasm